18F-FDG-PET/CT angiography in the diagnosis of infective endocarditis and cardiac device infection in adult patients with congenital heart disease and prosthetic material. (1st December 2017) - Pizzi, María N.; Dos-Subirà, L.; Roque, Albert; Fernández-Hidalgo, Nuria; Cuéllar-Calabria, Hug; Pijuan Domènech, Antonia; Gonzàlez-Alujas, María T.; Subirana-Domènech, M.T.; Miranda-Barrio, B.; Ferreira-González, Ignacio; González-López, Juan J.; Igual, Albert; et al.
Abstract: Objectives: Infective endocarditis (IE) and cardiac device infection (CDI) are a major complication in the growing number of patients with congenital heart disease (CHD) reaching adulthood. We aimed to evaluate the added value of 18 F-FDG-PET/CT angiography (PET/CTA) in the diagnosis of IE-CDI in adults with CHD and intravascular or intracardiac prosthetic material, in whom echocardiography (ECHO) and modified Duke Criteria (DC) have limitations because of the patients' complex anatomy. Methods: A prospective study was conducted in a referral center with multidisciplinary IE and CHD Units. PET/CTA and ECHO findings were compared in consecutive adult (≥ 18 years) patients with CHD who have prosthetic material and suspected IE-CDI. The initial diagnosis using the DC and the diagnosis with the additional PET/CTA data (DC + PET/CTA) were compared with the final diagnostic consensus established by an expert team at three months. Results: Between November-2012 and April-2017, 25 patients (15 men; median age 40 years) were included. Cases were initially classified as definite in 8 (32%), possible in 14 (56%) and rejected in 3 (12%). DC + PET/CTA allowed reclassification of 12/14 (86%) cases initially identified as possible IE. The sensitivity, specificity, PPV, NPV, and accuracy of DC at IE suspicion were 39.1%/83.3%/90.4%/25.5%/61.2%, respectively. The diagnostic performance increased significantly with addition of PET/CTA data: 87%/83.3%/95.4%/61.5%/85.1%, respectively. PET/CTA also provided an alternative diagnosis in 3 patients with rejected IE, and detected pulmonary embolisms in 3 patients. Conclusions: PET/CTA was a useful diagnostic tool in the complex group of adult patients with CHD who have cardiac or intravascular prosthetic material and suspected IE or CDI, providing added diagnostic value to the modified DC (increased sensitivity) and improving case classification.